2016
DOI: 10.5430/cns.v4n3p54
|View full text |Cite
|
Sign up to set email alerts
|

Effect of application of a Health Belief Model on changing mothers’ beliefs regarding birth spacing in rural areas

Abstract: Objective: A Health Belief Model seems promising as a framework for examining contraceptive behavior. The aim of this study was to examine the effect of application of a Health Belief Model on changing mothers' beliefs regarding birth spacing in rural areas. Methods: Design: A quasi experimental pre-post-test design was used to evaluate the effectiveness of application of a Health Belief Model on changing mothers' beliefs regarding birth spacing. Subjects: A simple random sample of 150 postpartum women were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
5
1
Order By: Relevance
“…This is congruent with Mohsen, 2016 (8) who study the effect of application of HBM on changing mothers' beliefs regarding birth spacing in rural areas and found that perception of seriousness of not using contraceptives of the sample is increased in the first post test than in the baseline. Also our study findings came in agrees with Mahmoodi et al,2011 (24) who found that the mean perceived severity scores before and after education were 45.38 ± 23.06 and 53.27 ± 1.21, respectively.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is congruent with Mohsen, 2016 (8) who study the effect of application of HBM on changing mothers' beliefs regarding birth spacing in rural areas and found that perception of seriousness of not using contraceptives of the sample is increased in the first post test than in the baseline. Also our study findings came in agrees with Mahmoodi et al,2011 (24) who found that the mean perceived severity scores before and after education were 45.38 ± 23.06 and 53.27 ± 1.21, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…The model can be adapted to counselling behaviour if one views complications as a state to avoid. Females vary in strength of desire to do premarital counselling and perception of costs and benefits of premarital counselling (8).…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that39.2% of Ghanaian women agreed that contraceptives use can make them infertile. As well as, the previously mentioned one conducted by (Mohsen et al, 2016).They reported that a minority of Egyptian women agreed that using contraceptives are negatively affected by far distance. Finally, the previously mentioned one conducted by (Asadisarvestani et al, 2017).…”
Section: Overall Health Beliefs Among Contraceptive Usersmentioning
confidence: 68%
“…This finding is congruent with the previously mentioned one conducted by (Frost & Lindberg, 2013).They reported that 63% of American women strongly agreed that using contraceptives organize family size. Also, (Mohsen et al, 2016) who conducted a study titled effect of application of a health belief model on changing mothers' beliefs regarding birth spacing in Egypt. They reported that all the study subjects strongly agreed that family planning helps decide desirable family size, 42.7% of them agreed that using contraceptives regulate menstrual cycle and 54.7% of them agreed that using contraceptives prevent many health problems and improve maternal health.…”
Section: Overall Health Beliefs Among Contraceptive Usersmentioning
confidence: 99%
“…5 Nursing curriculum includes variety of subjects taught in each year of the course among which midwifery nursing is one of the subject to be learnt. 6 Appropriate antenatal and intra-partum management is dependent on accurate assessment of in-utero fetal presentation, position and wellbeing with decisions regarding place, mode and position for delivery relying on correct assessment of fetal presentation and position. 7 Students may participate in Antenatal examination in various ways they may be involved in planning, implementing, administrating or evaluating, screening and testing programme or they may educate, assist and support the pregnant women to undergo regular antenatal examinations.…”
Section: Introductionmentioning
confidence: 99%